Comparison of Microgravity Analogs to Spaceflight in Studies of Plant Growth and Development - Kiss, John Z.; Wolverton, Chris; Wyatt, Sarah E.; Hasenstein, Karl H.; van Loon, Jack J.W.A. (Frontiers in Plant Science, 2019)
Life on Earth has evolved under the influence of gravity. This force has played an important role in shaping development and morphology from the molecular level to the whole organism. Although aquatic life experiences reduced gravity effects, land plants have evolved under a 1g environment. Understanding gravitational effects requires changing the magnitude of this force. One method of eliminating gravity’s influence is to enter into a free-fall orbit around the planet, thereby achieving a balance between centripetal force of gravity and the centrifugal force of the moving object. This balance often mistakenly referred to as microgravity but is best described as weightlessness. In addition to actually compensating gravity, instruments such as clinostats and random-positioning machines (RPM) have been used to eliminate effects of constant gravity on plant growth and development. However, these platforms do not reduce gravity but constantly change its direction. Despite these fundamental differences, there are few studies that have investigated the comparability between these platforms and weightlessness. Here, we provide a review of the strengths and weaknesses of these analogs for study of plant growth and development compared to spaceflight experiments. While these analogs are useful, the fidelity of the results relative to spaceflight depends on biological parameters and environmental conditions that cannot be simulated in ground-based studies.